Empowerment of MSEs through Business Contract Preparation Training with the Participatory Rural Appraisal (PRA) Method in Grogol Village - Muthia Sakti; Suherman, Suherman; Sulastri, Sulastri; Winriadirahman, Prameswara; Rika Aprilina; Erina Nur Afifa; Evan Dori; Marcy Euggeline Audreya; Aliya Sari; Isabel Maryam (Lembaga Teewan Journal Solutions, 2026)
Micro and Small Enterprises (MSEs) still face low legal literacy and the lack of use of written contracts in business activities, making them vulnerable to disputes and business losses. This community service activity aims to improve the understanding and skills of MSE actors in drafting simple business contracts through the Participatory Rural Appraisal (PRA) method. The activity was carried out in Grogol Village, West Jakarta involving 40 MSE actors. The PRA method is applied through the stages of problem identification, participatory planning, implementation of interactive training, and participatory evaluation. The training is carried out through contract law counseling, simulation of the preparation of business contracts, discussions on non-litigation dispute resolution, and the provision of Business Contract Pocket Books. Evaluation was carried out using pre-test and post-test to measure the increase in participants' capacity. The results showed an increase in participants' understanding of the function of business contracts, non-litigation dispute resolution, and the ability to draft simple contracts from 15% to 80%. This activity shows that the PRA method is effective in increasing legal literacy and business capacity of MSE actors in a participatory and sustainable manner.